Topology optimization of conductive heat transfer devices: An experimental investigation. (25th February 2018) - Subramaniam, V.; Dbouk, T.; Harion, J.-L.
Highlights: Experimental thermal measurements of optimal heat sinks. Experimental heat sinks obtained by topology optimization. Bi-material distribution in volume-to-point heat evacuation. Abstract: For optimal tree-like heat conductive structures obtained numerically by topology optimization (TO), few experimental investigations exist in the literature to author's knowledge. In this context, the present study deals with an experimental investigation of tree-like structures obtained by topology optimization (known also by bi-material volume-to-point problems). For a volume (of lower conductivity material) that is continuously generating heat, TO predicts tree-like structures (of higher conductivity material) to evacuate efficiently the amount of heat being generated. Experimental measurements were carried out on two tree-like structures using infrared thermography in order to test the validity of the developed numerical topology optimization approach. It is found that the experimental thermal measurements are in good agreement with numerical data obtained by TO, which was developed in this work by coupling the method of moving asymptotes (MMA) as optimization algorithm to the solid isotropic material with penalization (SIMP) as a bi-material distribution technique.